2022
DOI: 10.3233/jifs-212939
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: A representation of bifinite domains by rough approximable concepts

Abstract: In this paper, we introduce the notion of BF-contexts and show that the set of hyper-concepts of the BF-contexts is a bifinite domain. Conversely, given a bifinite domain we can obtain a BF-context such that all the hyper-concepts of it is isomorphic to the bifinite domain. Further, We obtain category equivalent to that of bifinite domains and BF-contexts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Wang et al ( 2023b ) proposed a self-adaptive fractional grey Euler model with dynamic accumulation order and used the model to forecast energy production of China. Yao et al ( 2022 ) studied the representation of bifinite domains by rough approximable concepts. Yan et al ( 2022 ) revealed a broadband vibration energy harvester based on nonlinear magnetic force and rotary pendulums.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al ( 2023b ) proposed a self-adaptive fractional grey Euler model with dynamic accumulation order and used the model to forecast energy production of China. Yao et al ( 2022 ) studied the representation of bifinite domains by rough approximable concepts. Yan et al ( 2022 ) revealed a broadband vibration energy harvester based on nonlinear magnetic force and rotary pendulums.…”
Section: Introductionmentioning
confidence: 99%